Association of New-Onset Seizures With SARS-CoV-2 Vaccines - Laela Sari, Laela Sari; Yusuf Indra, Yusuf Indra (The International Journal of Medical Science and Health Research, 2024)
Background: The association between new-onset seizures and SARS-CoV-2 vaccines has emerged as a significant area of inquiry, particularly as the global vaccination effort has expanded. Early insights into the neurological implications of COVID-19 itself laid the groundwork for understanding potential vaccine-related effects. Literature Review: The literature presents a nuanced understanding of the association between new-onset seizures and SARS-CoV-2 vaccines, revealing a complex interplay of neurological implications stemming from both the virus and the vaccination process. Initial investigations into COVID-19 highlighted the multifactorial nature of seizures as a potential manifestation of the virus, with studies emphasizing the need for heightened clinical awareness (Zareh-Shahamati et al., 2021). Subsequent research expanded on this foundation, examining the prevalence of seizures and status epilepticus in critically ill COVID-19 patients, thereby illustrating the significant neurological complications associated with the infection itself (A. Danoun et al., 2021). Conclusion: In conclusion, the collective body of research underscores the pressing need for ongoing studies to elucidate the mechanisms underlying the association between SARS-CoV-2 vaccines and new-onset seizures. This understanding is vital for informing clinical practice and ensuring the safety of vaccination efforts, particularly for populations at increased risk for neurological complications.